Efficacy and safety of tablet Ligashot in patients with ligament injury of knee and shoulder - Deb, Bijoy; Gobaloussamy, Bhuvanesh; Murugesan, Sakthibalan; Sivakumar, Gayathri (International Journal of Research in Orthopaedics, 2024)
Background: Ligament injuries of knee and shoulder disrupts joint homeostasis and leads to an imbalance between joint mobility and stability. Many drugs are available in the market for treating ligament injury grade 1 and 2 along with standard of care but there is still need for drugs with least adverse effects. So, in this study, an attempt has been done with tablet Ligashot, a nutraceutical for treating grade 1 and 2 ligament injury of knee and shoulder. Methods: This is an outcome, quasi-experimental study where patients with ligament injury of knee and shoulder were given tablet Ligashot daily for 3 months. A total of 30 male and female patients were included in the study. Changes from baseline to 12 weeks in pain intensity measured by pain visual analogue scale (VAS) and inflammatory markers (ESR, Hs CRP), MRI changes, time to return to pre-injury level of activity, patient reported physical function and quality of life (QoL) were assessed. Results: There was a statistically significant improvement after 12 weeks of treatment compared to baseline in VAS pain scale, time to return to pre-injury level of activity, patient reported physical function and in QoL questionnaire. There was also a statistically significant reduction in inflammatory markers-ESR and Hs-CRP (p<0.001). Conclusions: Ligashot tablet has proved to be safe and effective in the management of ligament injury of knee, shoulder joint by reducing inflammation, pain. It also improves visco-elasticity and participant’s functional capacity without causing any major side effects.